Surgeon! Withdraw in time! - Mykola Y. Polishchuk (Ukrainian Neurosurgical Journal, 2017)
You should fear of a young therapist and an old surgeon. Legislation should identify the critical age for operating surgeon, thereby reducing the effects of negative outcomes of interventions and potentiating the professional development of the young.